2007
DOI: 10.1248/jhs.53.671
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Studies on the Protective Effect of Betaine on Mitochondrial Function in Experimentally Induced Myocardial Infarction in Rats

Abstract: The present study was designed to examine the cardioprotective effect of betaine on mitochondrial function in isoprenaline-induced myocardial infarction in rats with respect to changes in the mitochondrial energy status and antioxidant defense system. Prior oral treatment with betaine significantly prevented the isoprenaline-induced elevation in the levels of diagnostic maker enzymes [alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and creatine phosphokinase (CPK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Glutathione functions by reaction with superoxide radicals, peroxy radicals and singlet oxygen, followed by the formation of oxidized glutathione and other disulphides (Aweda et al 2003). Depletion of GSH results in enhanced lipid peroxidation, and excessive lipid peroxidation can cause increased GSH consumption (Ganesan et al 2007a), as observed in the present study (Figs. 7 and 10).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Glutathione functions by reaction with superoxide radicals, peroxy radicals and singlet oxygen, followed by the formation of oxidized glutathione and other disulphides (Aweda et al 2003). Depletion of GSH results in enhanced lipid peroxidation, and excessive lipid peroxidation can cause increased GSH consumption (Ganesan et al 2007a), as observed in the present study (Figs. 7 and 10).…”
Section: Resultssupporting
confidence: 86%
“…Earlier, we reported the protective effect of betaine on mitochondrial function (Ganesan et al 2007a) protein and glycoprotein metabolism (Ganesan et al 2007b) and lipid metabolism (Ganesan et al 2008) and lysosomal function (Ganesan and Anandan 2009) against isoprenaline-induced myocardial infarction in rats. In the present study, an attempt was made to assess the protective effects of betaine against oxidative damage during experimentally induced restraint stress in Wistar albino rats with respect to changes in the levels of lipid peroxidation, antioxidant status (GST, GPx, CAT, SOD activities, and GSH level) in lymphoid organs of thymus and spleen, changes in the adrenal weight, plasma protein, and corticosterone levels.…”
Section: Introductionmentioning
confidence: 95%
“…The activity level of the enzyme iso-citrate dehydrogenase recorded significant depletion in the extract fed rats when compared with that of the control indicating the deranged oxidative potential in the sperm suspension. ICDH is a specific marker for the mitochondrial density [38] . The sperm motility showed a drastic depletion in the extract fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that betaine regulates erythrocyte (red blood cell) membrane ATPases via conformational changes, which results in cell volume control (Moeckel et al 2002). Earlier, we reported the protective effect of betaine on antioxidant status (Ganesan et al 2008b), mitochondrial function (Ganesan et al 2007a), protein and glycoprotein metabolism (Ganesan et al 2007b), and lipid metabolism (Ganesan et al 2008a) in isoprenaline-induced myocardial infarction in Wistar rats. In the present study, an attempt was made to assess the protective effects of betaine on isoprenaline-induced myocardial infarction with respect to changes in the levels of lysosomal enzymes and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 92%